Sintesis Lapisan Antikorosi Menggunakan Tanin Ekstrak Daun Ketapang (Terminalia Catappa L) sebagai Inhibitor dengan Metode Elektrodeposisi dan Pencelupan - Disgie Ulfika Loveanda; Dahyunir Dahlan (Universitas Andalas, 2021)
A research has been carried out on the effect of the Terminalia Catappa L extract Â as an inhibitor on the corrosion rate of commercial steel St-37. This study aims to form a layer on the steel surface. The coating using electrodeposition and immersion methods. The layers were made of 1 M CuSO4 solution, 0.24 M boric acid (H3BO3) and distilled water with the addition of Ketapang leaf extract at concentrations of 0%, 1%, 2%, 3%, 5%, 7%, 9% by volume in the electrodeposition method and 0%, 1%, 2%, 3%, 4% in the dyeing method. The characterization was carried out using an optical microscope and XRD characterization, while the corrosion rate and inhibition efficiency were obtained using the weight loss method. The optimum corrosion rate and efficiency of the inhibitor occurred at a variation of the inhibitor concentration of 3%. In the electrodeposition method the corrosion rate was 3.3 x 10-3 g/cm2.hour with 71% inhibition efficiency and in the immersion method the corrosion rate was 4.4 x 10-3 g/cm2.hour with 34% inhibition efficiency. The surface morphology of the steel coating using the electrodeposition and immersion methods obtained smooth and even results.Â